Telephone referrals by junior doctors: a randomised controlled trial assessing the impact of SBAR in a simulated setting. Issue 1045 (14th August 2012) - Cunningham, Neil James; Weiland, Tracey J; van Dijk, Julian; Paddle, Paul; Shilkofski, Nicole; Cunningham, Nicola Yumei
Abstract : Objective: To determine whether exposing junior doctors to S ituation, B ackground, A ssessment, R ecommendation (SBAR) improves their telephone referrals. SBAR is a standardised minimum information communication tool. Methods: A randomised controlled trial with participants and rating clinicians both blinded to group allocation. Hospital interns from a 2-year period (2006–2007) participated in two simulated clinical scenarios which required them to make telephone referrals. The intervention group was educated in SBAR between scenarios. Pre and post intervention telephone referrals were recorded, scored and compared. Six-month follow-up and year group comparisons were also made. An objective rating score measured the presence of specific 'critical data' communication elements on a scale of 1–12. Qualitative measures of global rating scores and participant self-rated scoring of performance were recorded. Time to 'first pitch' (the intern's initial speech) was also recorded. Results: Data were available for 66 interns out of 91 eligible. SBAR exposure did not increase the number of communication elements presented; objective rating scores were 8.5 (IQ 7.0–9.0) for SBAR and 8.0 (IQ 6.5–8.0) for the control group (p=0.051). Median global rating scores, designed to measure 'call impact', were higher following SBAR exposure (SBAR: 3.0 (IQR 2.0–4.0); control: 2.0 (IQ 1.0–3.0); p=0.003)). Global rating scores improved as time to 'first pitch' duration decreased (p=0.001). SBAR exposure did not improve time to 'first pitch' duration. Conclusion: In this simulated setting exposure to SBAR did not improve telephone referral performance by increasing the amount of critical information presented, despite the fact that it is a minimum data element tool. SBAR did improve the 'call impact' of the telephone referral as measured by qualitative global rating scores.